Metabolic optimization of the basketball free throw - Vando, S.; Padulo, J.; Migliaccio, G. M.; Attene, G.; Masala, D.; Falese, L.; Ardigò, L. P. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Due to its mixed physical-technical-tactical nature, basketball like other team sports needs attention on likely relationships between all its facets, e.g., metabolic power and technical skill. A common fundamental is the free throw (FT), which can be shot both when just come off the bench and when fatigued by previous actions. Our aim was to study the effect of different metabolic power values on successful FT percentage (FT%). Methods: 28 male (Under 17) basketball players (age 16.0±0.8 y, height 171±10 cm, mass: 60.5±9.2 kg, sport experience 7.9±1.0 yrs). The participants shot FT under three randomized testing sessions one week later than a Yo-Yo Intermittent Recovery test level 1 (Yo-Yo IR1) (Castagna et al., 2008) administered to measure HRMAX as a proxy of maximal metabolic power. All sessions consisted in 10 FT with 5-sec rest between subsequent FT, at different heart rates (HR): rest (0HR), after warm-up (HR at 50%HRMAX [50HR], 80%HRMAX [80HR]). The same procedure was repeated one week later to evaluate measures reliability. After 15` standard warm-up running each participants was administered 10 FT (with 5-sec rest intervals between subsequent FT) sessions at different intensities (0HR - 50HR - 80HR). Each intensity (HR monitored) was achieved by shuttle running (15+15 m). Reliability (Weir, 2005) of 0HR, 50HR and 80HR results was assessed by Intra-class Correlations Coefficient (ICC). A one-way within subjects ANOVA was performed to check for the differences between the three sessions with post-hoc Bonferroni test. The level of statistical significance was set at a p<0.05. Results: ICC showed a good reliability of 0HR (0.86), 50HR (0.88) and 80HR (0.95). Yo-Yo IR1 HRMAX was 198.0±6.9 bpm. ANOVA showed difference in FT% over sessions (F(1.26)=20.571 and p<0.0001) with 720 FT (r=-0.529 and p<0.0001). Bonferroni test did not show any significant 0HR-50HR FT% difference (-2% and p>0.05), while 80HR elicited significantly lower values with respect to both 0HR and 50HR (-23 and -22% and p<0.0001, respectively). Discussion: Our study provided two practical indications to keep high FT%: 1) no preliminary warm-up is needed, because the 0HR-50HR difference was not significant; and 2) 80HR decreases FT% significantly, providing therefore scientific support to the usual behavior by fouled players, who make use of all the allowed 30" to shoot each their FT.